Enhanced ammonium removal efficiency by ion exchange process of synthetic zeolite after Na+ and heat pretreatment - Ham, Kyujin; Kim, Beom Seok; Choi, Kwon Young (Water Science and Technology, 2018)
In this study, the optimum ammonium removal by activation of synthetic zeolite in the aqueous phase was investigated by batch ion exchange adsorption assay, and its surface changes due to activation modification was elucidated accordingly. Among the adsorbents examined, modified synthetic zeolite A-4 was the most effective at ammonium removal. The best activation condition of zeolite A-4 was established by Na+ and 300 °C heat treatment at pH around 6 to 7. Besides, the removal efficiency was investigated under various reaction conditions of pH, adsorbent dosage, stirring speed, and initial ammonium concentration. Finally, the adsorptive capacity Qe of synthetic zeolite A-4 activated by Na+ and heat treatment was determined as 31.9 mg/g at 1,000 mg-N/L of ammonium, whereas that of natural zeolite was measured as 16.0 mg/g. The obtained adsorption data was fitted to both Langmuir and Freundlich isotherm models, and the Langmuir isotherm model provided a better correspondence than the Freundlich isotherm. Finally, regeneration cycles for synthetic zeolite A-4 was determined for further industrial applications and efficient ammonium removal.
Keywords: Activation conditions; Ammonium concentrations; Ammonium removal; Ion-exchange adsorption; Langmuir and Freundlich isotherm models; Langmuir isotherm models; Regeneration; Synthetic zeolites; Adsorption; Ammonium Compounds; Hot Temperature; Hydrogen-Ion Concentration; Ion Exchange; Kinetics; Water Pollutants, Chemical; Water Purification; Zeolites; Ammonium removal; Ion exchange; Regeneration; Synthetic zeolite; Zeolite activation